The impact of activism on the performance of publicly-traded companies - Xavier, Wlamir Goncalves; Cesar Silva Melo, Lauro; Oliveira Camilo, Silvio Parodi; Greene, Frederick (Revista de Negócios, 2021)
Institutional investors hold the largest volume of financial resources in the world. The role of the institutional investor as a shareholder has evolved, and now institutional investors are engaged with increasing participation in companies. This active positioning, or activism, is defined as an increase of direct involvement by the investors in the management of companies and influence over corporate executives by vastly increased corporate governance. This paper proposes to analyze the impact of institutional investors' activism on the performance of publicly-traded companies in Brazil. The final sample composed of economic data from 351 companies. The financial and market performance was measured in the years from 2006 to 2015. For data analysis, a panel data effects model was chosen. Results suggest that the governance index moderates the effect of activism on performance, especially in companies where governance practices are not very developed.